Inventory System Improvement At PT Furniture Using The Dmaic Method - Okky Saputra; Yuanita Handayati (UNIVED Press, 2025)
PT Furniture is a company engaged in the distribution of goods located in Bandung, West Java. The company itself sells various products, in the field of home interiors. In the current system, the database owned by the company does not actually describe the number of goods owned by the company. The method used by the company to overcome this problem is the DMAIC method. In the DMAIC method, there are five stages carried out to solve the problem, namely define, measure, analyze, improve, and control. At the measure stage that has been carried out, it was found that the company had problems in the business process of purchasing goods, selling goods, and borrowing goods. From the business process owned by the company, ten root causes of failure were identified at the analyze stage. In the problems that occurred in the company, a proposal for improvement was made for the problematic business process. The proposed improvements are estimated to reduce the possibility of problems occurring in the company.